The Intersection between Leadership and Identity: Managing as a Counseling Center Director of Color. Issue 2 (3rd April 2022) - Chin, Calvin R.; Singleton, Karen; Juarez, Reina
ABSTRACT: Directors of color at college counseling centers face many challenges. In this article, three directors of color will describe the issues they face on a daily basis working in predominantly white institutions to illustrate how racial identities intersect with leadership. Included among the dynamics explored are the external pressures of unattainable expectations held by supervisors; microaggressions and negative stereotyping among peers; stereotype threat; and internal pressures around being undermined in racialized ways by staff; and managing projections and over-identifications among staff. We highlight the ways it can feel like walking a tightrope around serving the needs of a diverse staff. The article concludes by offering suggestions and next steps for supervisors of directors of color, staff of directors of color, and directors of color themselves.